A Hybrid Approach for Efficiently Illuminated Fabry-Pérot Cavity Antennas with Enhanced Bandwidth - Mateos-Ruiz, Pablo; Abdo-Sánchez, María Elena; Camacho-Peñalosa, Carlos (IEEE, 2025)
This contribution proposes a design methodology to realize Fabry-Perot cavity antennas with enhanced aperture efficiency and bandwidth. The proposed antenna employs a tapered Partially Reflective Surface (PRS) and leverages a com-bined approach incorporating principles from the simplified ray model and two-dimensional leaky-wave theory. By employing a transmission line model of the PRS, unit cells are selected that simultaneously satisfy the resonance condition, present a positive reflection phase slope, and synthesize the necessary leakage factor function. A design to obtain a uniform aperture distribution is carried out. The simulation results are compared against the best design from a previous study, thus showing the improvement realized by incorporating leaky-wave theory into the antenna design process.
Política de acceso abierto tomada de: https://conferences.ieeeauthorcenter.ieee.org/author-ethics/guidelines-and-policies/post-publication-policies/#posting (Requiere un embargo de 24 meses)
Keywords: Antenas; Fabry-Perot, Interferómetros de; Redes de banda ancha; Fabry-Pérot cavity antenna; Partially reflective surface; Leaky-wave; Spatial modulation; Enhanced bandwidth